2012
DOI: 10.1016/j.bbamcr.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cap-independent Nrf2 translation is part of a lipoic acid-stimulated detoxification stress response

Abstract: Little is known about either the basal or stimulated homeostatic mechanisms regulating nuclear tenure of Nf-e2-related factor 2 (Nrf2), a transcription factor that mediates expression of over 200 detoxification genes. Our data show that stress-induced nuclear Nrf2 accumulation is largely from de novo protein synthesis, rather than translocation from a pre-existing cytoplasmic pool. HepG2 cells were used to monitor nuclear Nrf2 24 hrs following treatment with the dithiol micronutrient (R)-α-lipoic acid (LA; 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 41 publications
5
53
0
1
Order By: Relevance
“…Meanwhile, Mn deficiency induced the high-abundance of Keap1 mRNA level in grass carp muscle, whereas optimal Mn supplementation resulted in the low-abundance of Keap1 gene expression in grass carp muscle. Moreover, it was reported that signaling molecule TOR up-regulated the Nrf2 expression in human hepatic carcinoma cells (Shay, Michels, Li, Kong, & Hagen, 2012). The results from the present study showed that Mn deficiency and excess both induced the low-abundance mRNA levels of TOR, whereas optimal dietary Mn supplementation up-regulated the TOR gene expression in grass carp muscle.…”
Section: Mn Up-regulated the Muscle Antioxidant-related Signaling Molsupporting
confidence: 59%
“…Meanwhile, Mn deficiency induced the high-abundance of Keap1 mRNA level in grass carp muscle, whereas optimal Mn supplementation resulted in the low-abundance of Keap1 gene expression in grass carp muscle. Moreover, it was reported that signaling molecule TOR up-regulated the Nrf2 expression in human hepatic carcinoma cells (Shay, Michels, Li, Kong, & Hagen, 2012). The results from the present study showed that Mn deficiency and excess both induced the low-abundance mRNA levels of TOR, whereas optimal dietary Mn supplementation up-regulated the TOR gene expression in grass carp muscle.…”
Section: Mn Up-regulated the Muscle Antioxidant-related Signaling Molsupporting
confidence: 59%
“…Our results indicated that 13.3 g kg −1 leucine supplementation down-regulated the expression of Keap1 gene in the muscle, suggesting that leucine may facilitate Nrf2 nuclear translocation to induce mRNA transcripts for SOD1, CAT and GPx, likely through down-regulating Keap1 gene expression in fish. In addition to stimulation of Nrf2 nuclear translocation, newly synthesized Nrf2 plays important role in Nrf2 nuclear accumulation (Shay et al, 2012). This author found that TOR was involved in the synthesis of Nrf2 protein in HepG2 cells.…”
Section: Protective Effect Of Leucine On Oxidative Damage In Musclementioning
confidence: 81%
“…Accordingly, there may be a close relationship between leucine and Nrf2, and Nrf2 may be involved in modulating gene expression of antioxidant enzymes regulated by leucine in fish muscle, which has not been investigated. Furthermore, mammalian target of rapamycin (mTOR) has been shown to regulate Nrf2 levels in HepG2 cells (Shay et al, 2012). Ribosomal protein S6 kinase 1 (S6K1), an effector of TOR, is sensitive to nutrients (Um et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these-such as lipoic acid-also boost translation of Nrf2 messenger RNA via an internal ribosome entry sequence (IRES) (Shay et al 2012). Hence, phase 2 inducers typically increase intracellular glutathione synthesis by increasing GCL transcription and expression.…”
Section: Strategies For Boosting Glutathione Synthesismentioning
confidence: 99%